REPUBLIC OF DAGHESTAN: THNOPOLITICAL AND ETHNOSOCIAL SITUATION AND THE RECENT CONFLICTS - TSAPIEVA, Olga; MUSLIMOV, Tagir (CENTRAL ASIA AND THE CAUCASUS, 2007)
Daghestan is a unique region of the Russian Federation: its past, culture, polyethnic and Poly confessional nature, climate and landscape, economic and demographic potential, as well as geostrategic and geographic location, set it apart from all the other regions of Russia. Its specific nature and key role on Russia’s southern borders have made it a special constituent of the Russian Federation. By the beginning of the democratic changes, the Republic of Daghestan (RD) had accumulated a heavy load of ethnic contradictions and conflicts. The Soviet policy of moving the highlanders down to the plains, which was carried out insistently and consistently, altered beyond repair the republic’s ethnic composition, which became even more varied and culturally diverse in the plains. Kumyks, Nogays, Chechen-Akkintsy, Azeris, and Russians, who formed compact ethnic groups, found themselves outnumbered by the newcomers (Avars, Darghins, Lakhs, and Lezghians). Tension between the old and new settlers and the latent conflicts between them were a natural result of the upturned balance. The situation was aggravated by the high level of migration outside the republic (to other CIS countries and Russian regions), as well as inside the republic (from the mountains to the plains and back), which is typical of Daghestan and caused by the surplus (up to 25 percent) workforce. The republic has people living in it who have still not been rehabilitated or reinstated on their own territory: this applies to the Chechen-Akkintsy and a large number of mountain-dwellers moved to Chechnia by force in 1944 and returned to their original place of residence in 1957. The assimilation policy regarding smaller ethnic groups was equally harmful While the Soviet Union was falling apart and the socioeconomic system undergoing radical changes, numerous hitherto suppressed local conflicts flared up to create new zones of confrontation and tension. Private life became less comfortable socially and politically, which forced people to keep within their ethnic groups and form ethnic public movements. They became part of the republic’s ethnopolitical context; more than that: they were more diverse than elsewhere: there were unitarian, separatist, ethno-confessional, nationalist, democratic, and other movements. Many of them consolidated on the ethno-corporate basis, a fact that spoke of politicized clans, tukhums, and social groups. All this created an ethnic paradox: internationalization of culture, on the one hand, and an obvious trend toward the national, on the other. The republic had 17 parties, 22 national and public political movements, 17 centers, and other associations.1 The movements formed with humanitarian, educational, and cultural centers, which set themselves the aim of reviving the local cultures, tongues, and traditions, betrayed a trend toward politics at a very early stage. Some of the local nations even went as far as falsifying their histories and distorting the past.